Rh(I)/(III)‐N‐Heterocyclic Carbene Complexes: Effect of Steric Confinement Upon Immobilization on Regio‐ and Stereoselectivity in the Hydrosilylation of Alkynes - Panyam, Pradeep K. R.; Atwi, Boshra; Ziegler, Felix; Frey, Wolfgang; Nowakowski, Michal; Bauer, Matthias; Buchmeiser, Michael R. (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Olefin Metathesis in Confinement: Towards Covalent Organic Framework Scaffolds for Increased Macrocyclization Selectivity - Emmerling, Sebastian T.; Ziegler, Felix; Fischer, Felix R.; Schoch, Roland; Bauer, Matthias; Plietker, Bernd; Buchmeiser, Michael R.; Lotsch, Bettina V. (Chemistry – A European Journal)
Covalent organic frameworks (COFs) offer vast structural and chemical diversity enabling a wide and growing range of applications. While COFs are well-established as heterogeneous catalysts, so far, their high and ordered porosity has scarcely been utilized to its full potential when it comes to spatially confined reactions in COF pores to alter the outcome of reactions. Here, we present a highly porous and crystalline, large-pore COF as catalytic support in α,ω-diene ring-closing metathesis reactions, leading to increased macrocyclization selectivity. COF pore-wall modification by immobilization of a Grubbs-Hoveyda-type catalyst via a mild silylation reaction provides a molecularly precise heterogeneous olefin metathesis catalyst. An increased macro(mono)cyclization (MMC) selectivity over oligomerization (O) for the heterogeneous COF-catalyst (MMC:O=1.35) of up to 51 % compared to the homogeneous catalyst (MMC:O=0.90) was observed along with a substrate-size dependency in selectivity, pointing to diffusion limitations induced by the pore confinement.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Potassium Ion Conductivity in the Cubic Labyrinth of a Piezoelectric, Antiferromagnetic Oxoferrate(III) Tellurate(VI) - Albrecht, Ralf; Hoelzel, Markus; Beccard, Henrik; Rüsing, Michael; Eng, Lukas; Doert, Thomas; Ruck, Michael (Chemistry – A European Journal)
Orange-colored crystals of the oxoferrate tellurate K12+6xFe6Te4−xO27 [x=0.222(4)] were synthesized in a potassium hydroxide hydroflux with a molar water–base ratio n(H2O)/n(KOH) of 1.5 starting from Fe(NO3)3 ⋅ 9H2O, TeO2 and H2O2 at about 200 °C. By using (NH4)2TeO4 instead of TeO2, a fine powder consisting of microcrystalline spheres of K12+6xFe6Te4−xO27 was obtained. K12+6xFe6Te4−xO27 crystallizes in the acentric cubic space group Iurn:x-wiley:09476539:media:chem202102464:chem202102464-math-0001 3d. [FeIIIO5] pyramids share their apical atoms in [Fe2O9] groups and two of their edges with [TeVIO6] octahedra to form an open framework that consists of two loosely connected, but not interpenetrating, chiral networks. The flexibility of the hinged oxometalate network manifests in a piezoelectric response similar to that of LiNbO3.The potassium cations are mobile in channels that run along the <111> directions and cross in cavities acting as nodes. The ion conductivity of cold-pressed pellets of ball-milled K12+6xFe6Te4−xO27 is 2.3×10^(−4) S ⋅ cm^(−1) at room temperature. Magnetization measurements and neutron diffraction indicate antiferromagnetic coupling in the [Fe2O9] groups.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Rh(I)/(III)‐N‐Heterocyclic Carbene Complexes: Effect of Steric Confinement Upon Immobilization on Regio‐ and Stereoselectivity in the Hydrosilylation of Alkynes - Panyam, Pradeep K. R.; Atwi, Boshra; Ziegler, Felix; Frey, Wolfgang; Nowakowski, Michał; Bauer, Matthias; Buchmeiser, Michael R. (Chemistry – A European Journal)
Rh(I) NHC and Rh(III) Cp* NHC complexes (Cp*=pentamethylcyclopentadienyl, NHC=N-heterocyclic carbene=pyrid-2-ylimidazol-2-ylidene (Py−Im), thiophen-2-ylimidazol-2-ylidene) are presented. Selected catalysts were selectively immobilized inside the mesopores of SBA-15 with average pore diameters of 5.0 and 6.2 nm. Together with their homogenous progenitors, the immobilized catalysts were used in the hydrosilylation of terminal alkynes. For aromatic alkynes, both the neutral and cationic Rh(I) complexes showed excellent reactivity with exclusive formation of the β(E)-isomer. For aliphatic alkynes, however, selectivity of the Rh(I) complexes was low. By contrast, the neutral and cationic Rh(III) Cp* NHC complexes proved to be highly regio- and stereoselective catalysts, allowing for the formation of the thermodynamically less stable β-(Z)-vinylsilane isomers at room temperature. Notably, the SBA-15 immobilized Rh(I) catalysts, in which the pore walls provide an additional confinement, showed excellent β-(Z)-selectivity in the hydrosilylation of aliphatic alkynes, too. Also, in the case of 4-aminophenylacetylene, selective formation of the β(Z)-isomer was observed with a neutral SBA-15 supported Rh(III) Cp* NHC complex but not with its homogenous counterpart. These are the first examples of high β(Z)-selectivity in the hydrosilylation of alkynes by confinement generated upon immobilization inside mesoporous silica.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Fundamental Characterization, Photophysics and Photocatalysis of a Base Metal Iron(II)‐Cobalt(III) Dyad - Huber-Gedert, Marina; Nowakowski, Michał; Kertmen, Ahmet; Burkhardt, Lukas; Lindner, Natalia; Schoch, Roland; Herbst‐Irmer, Regine; Neuba, Adam; Schmitz, Lennart; Choi, Tae‐Kyu; Kubicki, Jacek; Gawelda, Wojciech; et al. (Chemistry – A European Journal)
Keywords: Photocatalytic Hydrogen Production; Catalysis; Inorganic Chemistry

Crystallization and Organic Field‐Effect Transistor Performance of a Hydrogen‐Bonded Quaterthiophene - Gebers, Jan; Özen, Bilal; Hartmann, Lucia; Schaer, Michel; Suàrez, Stéphane; Bugnon, Philippe; Scopelliti, Rosario; Steinrück, Hans-Georg; Konovalov, Oleg; Magerl, Andreas; Brinkmann, Martin; Petraglia, Riccardo; et al. (Chemistry – A European Journal)

Self‐Assembly of Pseudo‐Isocyanine Chloride as a Sensor for Macromolecular Crowding In Vitro and In Vivo - Hämisch, Benjamin; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Self‐Assembly of Pseudo‐Isocyanine Chloride as a Sensor for Macromolecular Crowding In Vitro and In Vivo - Hämisch, Benjamin; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Potential Precursor Alternatives to the Pyrophoric Trimethylaluminium for the Atomic Layer Deposition of Aluminium Oxide - Mai, Lukas; Boysen, Nils; Zanders, David; de los Arcos, Teresa; Mitschker, Felix; Mallick, Bert; Grundmeier, Guido; Awakowicz, Peter; Devi, Anjana (Chemistry – A European Journal)

Gold(II) Porphyrins in Photoinduced Electron Transfer Reactions - Preiß, Sebastian; Päpcke, Ayla; Burkhardt, Lukas; Großmann, Luca; Lochbrunner, Stefan; Bauer, Matthias; Opatz, Till; Heinze, Katja (Chemistry – A European Journal)

Undiscovered potential: Ge catalysts for lactide polymerization - Herres-Pawlis, Sonja; Rittinghaus, Ruth D.; Tremmel, Jakub; Ruzicka, Ales; Conrads, Christian; Albrecht, Pascal; Hoffmann, Alexander; Ksiazkiewicz, Agnieszka; Pich, Andrij; Jambor, Roman (Chemistry – A European Journal)

Potential Precursor Alternatives to the Pyrophoric Trimethylaluminium for the Atomic Layer Deposition of Aluminium Oxide - Mai, Lukas; Boysen, Nils; Zanders, David; de los Arcos de Pedro, Maria Teresa; Mitschker, Felix; Mallick, Bert; Grundmeier, Guido; Awakowicz, Peter; Devi, Anjana (Chemistry – A European Journal)

Excited‐State Kinetics of an Air‐Stable Cyclometalated Iron(II) Complex - Steube, Jakob; Burkhardt, Lukas; Päpcke, Ayla; Moll, Johannes; Zimmer, Peter; Schoch, Roland; Wölper, Christoph; Heinze, Katja; Lochbrunner, Stefan; Bauer, Matthias (Chemistry – A European Journal)

Inside Cover: Structure–Reactivity Relationship in the Frustrated Lewis Pair (FLP)‐Catalyzed Hydrogenation of Imines (Chem. Eur. J. 22/2016) - Tussing, Sebastian; Kaupmees, Karl; Paradies, Jan (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Base‐Free Non‐Noble‐Metal‐Catalyzed Hydrogen Generation from Formic Acid: Scope and Mechanistic Insights - Mellmann, Dörthe; Barsch, Enrico; Bauer, Matthias; Grabow, Kathleen; Boddien, Albert; Kammer, Anja; Sponholz, Peter; Bentrup, Ursula; Jackstell, Ralf; Junge, Henrik; Laurenczy, Gábor; Ludwig, Ralf; et al. (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Porous Metal Oxides as Gas Sensors - Tiemann, Michael (Chemistry - A European Journal)
Semiconducting metal oxides are frequently used as gas-sensing materials. Apart from large surface-to-volume ratios, well-defined and uniform pore structures are particularly desired for improved sensing performance. This article addresses the role of some key structural aspects in porous gas sensors, such as grain size and agglomeration, pore size or crack-free film morphology. New synthesis concepts, for example, the utilisation of rigid matrices for structure replication, allow to control these parameters independently, providing the opportunity to create self-diagnostic sensors with enhanced sensitivity and reproducible selectivity.

Straightforward Synthesis of (R)-(−)-Kjellmanianone - Christoffers, Jens; Werner, Thomas; Frey, Wolfgang; Baro, Angelika (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Structural Investigation of High-Valent Manganese–Salen Complexes by UV/Vis, Raman, XANES, and EXAFS Spectroscopy - Feth, Martin P.; Bolm, Carsten; Hildebrand, Jens P.; Köhler, Manuela; Beckmann, Oliver; Bauer, Matthias; Ramamonjisoa, Rivo; Bertagnolli, Helmut (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry